Study of Vegetative Propagation on Intsia bijuga (Colebr.) O.K. with Grafting - andi Sukendro; Irdika Mansur; Risna Trisnawati (Jurnal Silvikultur Tropika, 2010)
Vegetative propagation by grafting is an alternative method for merbau [Instia bijuga (Colebr.) O.K] propagation. One of the advantages of grafting that is  mostly used in seed production  that will be planted in seed orchard and it is useful for saving the merbau genetics. The research used Top Cleft Grafting method and completely randomized design with two factors. The first  factor is rootstock treatment which has diameter between 4-6 mm and 6.1-8 mm. The second factor is a scion phase type treatment which has dormant type and active type. Based on ANOVA, it is known that the rootstock and scion phase type treatments do not have significant influence on survival percentage and disease resistance percentage. But, interaction between them have a significant influence on a disease resistance percentage. According to the result of research, it is  known that the average of survival percentage of  Merbau grafting is 21.67%.